"The City as Muse": A Context-Oriented Meta-Historical Reading of Toyin Falola's A Mouth Sweeter than Salt - Ibrahim A. Odugbemi (Yoruba Studies Review)
A number of scholarly and critical arguments have explored the poetics of nonfiction, otherwise called life writing, as a sub-genre of prose literature. Against the common expectation of a detailed concentration on facts about the subject (the self or the other) which has made nonfiction to be seen in some quarters as a concern of history, such critical arguments have shown that this genre has its peculiar, predominant pattern and structure, which make it arguably a concern of the literary enterprise. A part of such arguments theoretically postulates that nonfiction is a meta-history, based on its identification of some textual and contextual properties and patterns of narration which transform the life account of the self or other into a meta-historical (and not historical) expression, and therefore makes such writing a concern of literature. In extension of this argument, this paper examines Toyin Falola's memoir, A Mouth Sweeter than Salt, as a genre of life writing and, especially, a form of autobiography, by showing how the setting, Ibadan, in its cultural and social formations, is depicted as having contributed to the self-awareness, self-image and identity of the subject, and how this reflection makes the narrative a meta-historical expression.